2011
DOI: 10.1002/cncr.25978
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of immunophenotypic and karyotypic features of Philadelphia positive B‐lymphoblastic leukemia in the era of tyrosine kinase inhibitors

Abstract: Background Philadelphia (Ph) positive B-lymphoblastic leukemia exhibits immunophenotypic, karyotypic, and molecular genetic heterogeneity. The prognostic significance of these parameters was assessed in the context of intensive tyrosine kinase inhibitor (TKI)-based chemotherapy. Methods We studied 65 cases of adult Ph-positive ALL treated with TKI-based therapy, correlated their clinicopathologic heterogeneity with patient outcome, and compared the findings with 60 cases of adult diploid B-ALL treated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 91 publications
2
28
2
1
Order By: Relevance
“…9 All precursor B-ALL cases expressed CD19 in conjunction with at least one other B-lineage marker (CD22, CD79a, and/or cIgM), and were negative for cCD3 and myeloproxidase. These results were essential to confirm a diagnosis of precursor B-ALL.…”
Section: Flow Cytometric Immunophenotypingmentioning
confidence: 92%
See 1 more Smart Citation
“…9 All precursor B-ALL cases expressed CD19 in conjunction with at least one other B-lineage marker (CD22, CD79a, and/or cIgM), and were negative for cCD3 and myeloproxidase. These results were essential to confirm a diagnosis of precursor B-ALL.…”
Section: Flow Cytometric Immunophenotypingmentioning
confidence: 92%
“…8 Patients with Ph-positive precursor B-ALL were treated with the hyper-CVAD regimen concurrently with either imatinib mesylate or dasatinib as previously reported. 9 Treatment was not different for patients with either secondary or de novo precursor B-ALL.…”
Section: Study Groupmentioning
confidence: 96%
“…However, in their separate analysis, including only patients allografting in first CHR, this additional aberration was not correlated with outcome. Another study from Jaso et al 8 has also showed no adverse prognostic factors to allow risk stratification. Main limitations of these studies were the short follow-up duration (o3 years) and lack of analysis regarding the role of minimal residual disease (MRD) monitoring.…”
Section: Introductionmentioning
confidence: 95%
“…This finding compared to older studies prior to use of Imatinib in Ph+ ALL showed that Ph+ patients had poorer outcome. [7][8][9] International Journal of Hematology and Oncology Concerning Molecular response (MR), in the present study after receiving chemotherapy accompanied with Imatinib, minor BCR-ABL fusion gene was expressed in mRNA of patient leukocyte (Mean ± SD = 0.006± 0.006), with a 3 log reduction from baseline ratio. This is in accordance with the results previously reported that when Imatinib is added to induction therapy, minor BCR-ABL , mRNA was reduced at least 1 log from baseline after the first induction therapy.…”
mentioning
confidence: 61%